2017
DOI: 10.1080/10550887.2017.1303980
|View full text |Cite
|
Sign up to set email alerts
|

Positive association of personal distress with testosterone in opiate-addicted patients

Abstract: Clinical studies report that substance addictions are associated with sociocognitive impairments. Regarding opiate-addicted patients, the few existing studies point to deficits in empathic abilities. Previous research suggests that testosterone might be a relevant biomarker of these impairments. The authors aimed to investigate whether opiate-addicted patients show specific impairments in emotional (empathic concern, personal distress) and cognitive empathy compared to healthy controls. Furthermore, the author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…The finding of lower emotional empathy in the nonintoxicated users partially replicates previous research suggesting impaired empathy among drug users (Ferrari et al 2014;Kroll et al 2018aKroll et al , 2018bMaurage et al 2011;Preller et al 2014) and opioid users specifically (Kroll et al 2018a;Stange et al 2017;Tomei et al 2017), but crucially highlighted that acutely intoxicated opioid users show intact emotional empathy compared to controls. This was contrary to our initial prediction that empathy would be lowest within the intoxicated user group.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The finding of lower emotional empathy in the nonintoxicated users partially replicates previous research suggesting impaired empathy among drug users (Ferrari et al 2014;Kroll et al 2018aKroll et al , 2018bMaurage et al 2011;Preller et al 2014) and opioid users specifically (Kroll et al 2018a;Stange et al 2017;Tomei et al 2017), but crucially highlighted that acutely intoxicated opioid users show intact emotional empathy compared to controls. This was contrary to our initial prediction that empathy would be lowest within the intoxicated user group.…”
Section: Discussionsupporting
confidence: 84%
“…Impairments in emotional empathy have been observed in drug users generally (Ferrari et al 2014), alcohol users (Maurage et al 2011) and stimulant users (Kroll et al 2018a(Kroll et al , 2018bPreller et al 2014). Two studies with chronic opioid users have similarly reported impairments in emotional empathy using a subjective questionnaire among methadoneand diacetylmorphine-maintained individuals (Stange et al 2017;Tomei et al 2017) but a further study failed to replicate these findings (Kroll et al 2018a). The ability to empathise can be affected by situational factors including psychosocial stress, affective state, and socioeconomic status (Kanske et al 2017), where acute opioid intoxication state may also be important to understand impairments in empathy within the context of wider social stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IRI has been used in many trials related to social cognition (427) (e.g., 329, 427429) and neurophysiological studies (430, 431), in combination with MRI data (432–437), and appears to be predictive of performance on other tasks of social cognition (438440). Atypical scores may arise in association with schizotypy (441), schizophrenia (256, 442448), epilepsy (449, 450), ASD (156), Huntington’s disease (183, 184), Tourette syndrome (183), Alzheimer’s disease and mild cognitive impairment (451), frontotemporal dementia (452454), post-traumatic stress disorder (455, 456), attention deficit-hyperactivity disorder (393), anorexia nervosa (457), Parkinson’s disease (458, 459), depression (273), traumatic brain injury (460), aphasia (461), multiple sclerosis (462), complex regional pain (463), and substance misuse (464). No significant difference to controls have also been found in other samples of patients with substance misuse (25, 26, 465), schizophrenia (466), first-episode psychosis (467), and first-degree relatives of patients with schizophrenia (468, 469).…”
Section: Resultsmentioning
confidence: 99%